2003
DOI: 10.2337/diacare.26.9.2536
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Screening for Pre-diabetes Among U.S. Adults

Abstract: OBJECTIVE -We evaluated various strategies to identify individuals aged 45-74 years with pre-diabetes (either impaired glucose tolerance or impaired fasting glucose). RESEARCH DESIGN AND METHODS -We conducted a cost analysis to evaluate the effectiveness (proportion of cases identified), total costs, and efficiency (cost per case identified) of five detection strategies: an oral glucose tolerance test (OGTT), a fasting plasma glucose (FPG) test, an HbA 1c test, a capillary blood glucose (CBG) test, and a risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 14 publications
1
44
1
Order By: Relevance
“…Zhang and colleagues 204 addressed a similar question to that of Icks and colleagues. 201 However, they assessed the efficacy, effectiveness and efficiency of various strategies for detecting both cases of prediabetes (IGT and/or IFG) and cases of undiagnosed diabetes.…”
Section: The Studiesmentioning
confidence: 90%
See 3 more Smart Citations
“…Zhang and colleagues 204 addressed a similar question to that of Icks and colleagues. 201 However, they assessed the efficacy, effectiveness and efficiency of various strategies for detecting both cases of prediabetes (IGT and/or IFG) and cases of undiagnosed diabetes.…”
Section: The Studiesmentioning
confidence: 90%
“…The searches identified five studies for inclusion in this section of the review [201][202][203][204][205] These studies are summarised in Table 16 and discussed in detail below.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Previous studies have shown that women treated for chronic HF are more likely than men to have HF with preserved ejection fraction (HFPEF). 5,8 A large proportion of women who are admitted for acute decompensated HF have preserved systolic function with many comorbidities. 9 In addition, clinical outcomes among women with HF have not improved at the same rate as those seen in men.…”
Section: Epidemiologymentioning
confidence: 99%